Management Implementation In Education - Apriyani, Nur (Jurnal Diskursus Islam, 2023)
Learning is a way to improve the quality of human resources for the better. In this increase in human energy resources, learning plays a very significant role in the quality improvement process because the increase in human energy resources cannot be separated from the process of increasing the quality of learning. The principles of learning management are the main guidelines or guidelines for implementing a series of managerial activities that ensure the success or failure of learning institutions, namely schools. The four significant aspects that become the concern in implementing the principles of learning management are the objectives to be achieved, the subject (people who participate in it), the tasks carried out, and the values ​​that apply in the organization/institution. Implementation of management in the field of learning includes input , process, output and outcome. Learning input is declared qualified when it is ready to process. The learning process is quality if it is able to produce an educational atmosphere that is active, innovative, creative and fun. And the output is declared quality if the academic and non-academic learning outcomes of major students are declared quality. Abstrak Pembelajaran merupakan sesuatu metode dalam meningkatkan mutu sumber energi manusia menjadi lebih baik. Dalam peningkatan sumber energi manusia ini, pembelajaran memegang peranan yang sangat berarti dalam proses peningkatan kualitas sebab peningkatan sumber energi manusia tersebut tidak dapat dipisahkan dengan proses peningkatan kualitas pembelajaran. Prinsip-prinsip pembelajaran manajemen merupakan pedoman ataupun pegangan utama penerapan serangkaian kegiatan manajerial yang memastikan keberhasilan ataupun kegagalan lembaga pembelajaran adalah sekolah. Empat aspek berarti yang jadi perhatian dalam mengimplementasikan prinsip-prinsip manajemen pembelajaran merupakan tujuan yang hendak dicapai, subjek (orang-orang yang ikut serta di dalamnya), tugas yang diemban, serta nilai-nilai yang berlaku dalam organisasi/lembaga tersebutimplementasi manajemen di bidang pembelajaran meliputi input, proses, output dan outcome. Input pembelajaran dinyatakan bermutu bila siap berproses. Proses pembelajaran bermutu apabila mampu menghasilkan atmosfer pendidikan yang aktif, inovatif serta kreatif dan menyenangkan Serta keluaran dinyatakan bermutu bila hasil belajar akademik dan non akademik siswa besar Hasil dinyatakan bermutu apabila lulusan kilat terserap di dunia kerja serta seluruh pihak mengakui kehebatan lulusan serta merasa puas.